Detection of E119V and E119I Mutations in Influenza A (H3N2) Viruses Isolated from an Immunocompromised Patient: Challenges in Diagnosis of Oseltamivir Resistance - Okomo-Adhiambo, Margaret (American Society for Microbiology (ASM), 2010)
The clinical use of the neuraminidase inhibitor (NAI) oseltamivir is associated with the emergence of drug resistance resulting from subtype-specific neuraminidase (NA) mutations. The influenza A/Texas/12/2007 (H3N2) virus isolated from an oseltamivir-treated immunocompromised patient exhibited reduced susceptibility to oseltamivir in the chemiluminescent neuraminidase inhibition (NI) assay (∼60-fold increase in its 50% inhibitory concentration [IC(50)] compared to that for a control virus). When further propagated in cell culture, the isolate maintained reduced susceptibility to oseltamivir in both chemiluminescent and fluorescent NI assays (∼50- and 350-fold increases in IC(50), respectively). Sequencing analysis of the isolate revealed a mix of nucleotides coding for amino acids at position 119 of the NA [E119(V/I)]. Plaque purification of the isolate yielded E119V and E119I variants, both exhibiting reduced susceptibility to oseltamivir. The E119I variant also showed decreased susceptibility to zanamivir and the investigational NAIs peramivir and A-315675. The emergence of E119V variants in oseltamivir-treated patients has been previously reported; however, the E119I mutation detected here is a novel one which reduces susceptibility to several NAIs. Both mutations were not detected in unpropagated original clinical specimens using either conventional sequencing or pyrosequencing, suggesting that these variants were present in very low proportions (<10%) in clinical specimens and gained dominance after virus propagation in MDCK cells. All virus isolates recovered from the patient were resistant to adamantanes. Our findings highlight the potential for emergence and persistence of multidrug-resistant influenza viruses in oseltamivir-treated immunocompromised subjects and also highlight challenges for drug resistance diagnosis due to the genetic instability of the virus population upon propagation in cell culture.